EFFICIENCY OF SCHOOL FINANCIAL MANAGEMENT AND ITS IMPACT ON IMPROVING THE QUALITY OF TEACHING AND LEARNING - Erwin Erwin; Farida Asy'ari; Retno Winarni (Adisam Publisher, 2025)
School financial management efficiency is the practice of managing the financial resources of educational institutions in a targeted and cost-effective manner to support the implementation of teaching and learning activities. By optimizing the use of funds, schools can improve the availability and quality of educational facilities, learning technology and teacher professional development, which directly impacts on improving the quality of teaching and learning. This efficiency not only improves students' academic performance but also adds value to the school's reputation, which is important for its long-term financial and academic sustainability. The research method used in this study is the literature research method by adjusting to the context of the research. shows that efficiency in financial management allows for better resource allocation, which directly supports the provision of good learning facilities, professional development for teachers, as well as the integration of advanced educational technology. The research also highlights how responsible financial management contributes to the reputation of educational institutions, which stimulates increased financial support and strengthens the sustainability of school operations. The conclusions of this study support the idea that efficient financial management is of key importance in creating an environment conducive to improved teaching and learning quality, which in turn will have a positive impact on students' educational outcomes. This research provides important insights for education policy makers and school practitioners in designing financial management strategies that can improve the quality of education.